Estelle L’Hardy’s Ecstatic State and Jenny Wren’s Blessed Children: Dickens’s Invention within the Evolving Mental Sciences - Carole Koepke Brown (Cahiers Victoriens et Edouardiens)
In Our Mutual Friend, Dickens brilliantly exploits the medical climax in the recovery of the ‘incurable’ Estelle L’Hardy (1836–37), a paralyzed Swiss girl who self-hypnotized a celestial choir to assuage menacing pain. When the French doctor and pioneer Antoine Despine finally learned of her nightly choir, he recalled his clinical experience with former patients who had presented with ecstasy (occasionally a symptom of hysteria). Despine had successfully treated them with mesmerism, so he added mesmerism to Estelle’s treatment plan. Within months, Estelle walked. Over the centuries a French doctor, a Swiss doctor, and an American doctor championed Despine. They deepened the understanding of this cohort of bewildering patients who generally have an early history of overwhelming, chronic trauma and develop hysteria or double consciousness, later called multiple personalities (or identities) now termed dissociative identity disorder. In his idiosyncratic way, Dickens is aligned with these three doctors. A circumstantial case proposes that Dickens (two close friends were familiar with the Estelle case) worked strategic variations on Estelle’s case to heighten the drama in Fanny Cleaver/Jenny Wren’s story of her ecstatic state in which the blessed children would comfort her. Dickens identified the reserves of transformational energy in Estelle’s ecstasy and harnessed them for Fanny-Jenny—adding, heightening, dropping elements from the Estelle case—as he improvised his small seamstress.